Avaliação da resposta imunológica desencadeada em camundongos por diferentes isolados de Neospora caninum - Maia, Lydiane Parreira (2015)
Neospora caninum is a protozoan of the Apicomplexa phylum that affects several domestic and wild animals. This parasite cause neuromuscular commitment canines and abortion in bovines due to vertical transmission, respectively. A considerable economic loss in cattle production is due to this abortion. Additionally, it was found that different isolates of the parasite can induce distinct immune responses. Thus, this study aimed to compare the immune response profile and virulence triggered by Nc-1 and Nc-Liv strains of N. caninum. Both isolates were cultivated in HeLa cells and inoculated intraperitoneally in mice C57BL/6. For the survival assays, mice were infected with 1x107 tachyzoites of Nc-1 or Nc-Liv strains. It was observed a survival of 50% in the group infected with Nc-Liv. Mortality was not recorded in mice infected with Nc 1. Additionally, we found an increased weight loss in animals infected with Nc-Liv in comparison with the group infected with Nc-1. During acute phase of infection (7 days) a significant difference in peritoneal parasitism was identified, as well as in brain parasitism in the chronic phase of disease (30 days), evidenced by an enhanced number of DNA genomic copies found in each tissue. However, no significant differences were found in samples of lungs and liver during acute infection. The pattern of cytokine production demonstrated an induction of cytokines of Th1 response (IL-12, IFN-γ e NO) in a similar concentration in samples from the peritoneal fluids, lungs, livers (7 days) and brains (30 days). Nevertheless, the serum concentration of cytokines showed that mice infected with Nc-Liv also induced cytokines from Th2 (IL-4) e Th17 (IL-23 e IL-17A) profile. Moreover, an enhanced neutrophil recruitment was observed by Nc-Liv strain in comparison Nc-1.Thus, we conclude that Nc-Liv isolate possess an increased virulence in relation to Nc-1, which may be due to the induction of a mixed Th1/Th2/Th17 pattern of cytokines during the infection.